Production and characterisation of bacterial cellulose/ metal organic framework composite structures for CO2 adsorption - Çiçekli, Gaye (My University, 2022)
The discharge of pollutants into the atmosphere that are both harmful to human health and the environment as a result of natural and industrial activity is referred to as air pollution. A large increase in atmospheric CO2 has been attributed as the primary causes of climate change, which is damaging our planet, since the industrial revolution. Physico-chemical properties of metal organic frameworks (MOFs) have been the focus of various studies for their usage as a hybrid material in a range of industries. This highly organised porous substance is made up of various organic ligands and metal ions. It can be used in many applications, especially CO2 adsorption, by making various combinations and modifications. MOFs' organic building blocks are manufactured from nonrenewable petroleum feedstock, which limits their utility in biological applications because to their intrinsic toxicity and nonbiodegradability. The addition of natural polysaccharide improves the composite material's compatibility and flexibility. Bacterial cellulose has sparked interest as a “green building block” for membranes thanks to its matchless features, including as biocompatibility and high mechanical strength. Multifunctional cellulose–MOF integrated composite membranes can be employed on their own to absorb CO2 and provide a healthier living conditions. In this study, Bacterial Cellulose@ ZIF-8, Bacterial Cellulose @ZIF-67 and Bacterial Cellulose @ ZIF8-67 composites were produced for CO2 adsorption. The chemical, morphological, antibacterial properties and CO2 adsorption properties of these composites have been researched. This thesis describes a method for making membrane composite materials that can adsorb CO2 molecules.

Hava kirliliği, doğal ve endüstriyel faaliyetler sonucunda hem insan sağlığına hem de çevreye zararlı maddelerin atmosfere salınmasıdır. Gezegenimize zarar veren küresel ısınmanın başlıca nedeni olarak atmosferik CO2 görülmektedir. Metal organik çerçevelerin (MOF'lar) fiziko-kimyasal özellikleri, bir hibrit malzeme olarak bir dizi alanda birçok araştırmaya konu olmuştur. Bu oldukça düzenli gözenekli malzeme, farklı organik ligandların ve metal iyonlarının bir araya getirilmesiyle oluşturulmakta ve çeşitli kombinasyon ve modifikasyonların yapılabilmesi ile CO2 adsorpsiyonu başta olmak üzere pek çok uygulamada kullanılabilmektedir. MOF'ların organik yapı taşları, doğal toksisite ve biyolojik olarak parçalanamama sebepleriyle, biyolojik sektördeki uygulamalarını sınırlayan yenilenemeyen petrol hammaddelerinden elde edilir. Bu nedenle, selüloz lifler gibi yenilenebilir ve sürdürülebilir hammaddelerin kullanılması önemlidir. MOF sınıfına, doğal olarak oluşan polisakkaritin dahil edilmesi, ortaya çıkan hibrit malzemeye biyolojik uyumluluk ve esneklik kazandırır. Bakteriyel selüloz, yüksek mekanik mukavemet ve iyi biyouyumluluk gibi bazı istisnai özellikler nedeniyle giderek artan bir ilgi çekmiştir. Çok işlevli selüloz-MOF içeren kompozit membranlar, CO2’yi emmek ve daha sağlıklı bir yaşam ortamı elde etmek için kullanılabilir. Bu çalışmada CO2 adsorpsiyonu için Bakteriyel Selüloz@ZIF-8, Bakteriyel Selüloz@ZIF-67 ve Bakteriyel Selüloz@ZIF8-67 kompozitleri üretilmiştir. Bu kompozitlerin mekanik, kimyasal, morfolojik ve antibakteriyel özellikleri ile CO2 adsorpsiyon özellikleri incelenmiş olup bu çalışma, CO2 moleküllerini adsorbe edebilen membran kompozit malzemelerinin hazırlanması için uygun bir yöntem sunmaktadır.
CO2 adsorspsiyonu için bakteriyel selüloz/ metal organik çerçeve kompozit yapıların üretimi ve karakterizasyonu
Keywords: Bacterial Cellulose; Bioengineering; Biyomühendislik; CO2 Adsorpsiyonu; CO2 Adsorption; Metal Organic Framework Bakteriyel Selüloz; Metal Organik Çerçeve